Activity of cefiderocol (S-649266) against carbapenem-resistant Gram-negative bacteria collected from inpatients in Greek hospitals. (22nd March 2017) - Falagas, Matthew E.; Skalidis, Tilemachos; Vardakas, Konstantinos Z.; Legakis, Nicholas J.; ,
Abstract : Background: Cefiderocol (S-649266), a siderophore cephalosporin, utilizes a novel mechanism of entry into the periplasmic space of Gram-negative bacteria and is broadly stable to ESBLs and carbapenemases. Methods: A collection of carbapenem-resistant Gram-negative bacteria isolated from clinical specimens in 18 Greek hospitals was tested for susceptibility to cefiderocol, meropenem, ceftazidime, cefepime, ceftazidime/avibactam, ceftolozane/tazobactam, aztreonam, amikacin, ciprofloxacin, colistin and tigecycline. Broth microdilution plates were used to determine MICs. Results: In total 189 non-fermentative Gram-negative bacteria (107 Acinetobacter baumannii and 82 Pseudomonas aeruginosa ) and 282 Enterobacteriaceae (including 244 Klebsiella pneumoniae, 14 Enterobacter cloacae and 11 Providencia stuartii ) were studied. For both A. baumannii and P. aeruginosa the MIC90 of cefiderocol was 0.5 mg/L. For K. pneumoniae, E. cloacae and P. stuartii the MIC90 of cefiderocol was 1, 1 and 0.5 mg/L, respectively. Tigecycline was the second most active antibiotic, followed by colistin. Conclusions: Cefiderocol exhibited greater antimicrobial activity in vitro against carbapenem-resistant Gram-negative bacteria than comparator antibiotics.